Business Plan Proposal Preparation Training to Improve Student Understanding in Starting a Business - Shanti Nugroho Sulistyowati; Fahimul Amri (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The number of Indonesian entrepreneurs is still limited, the number of entrepreneurs in Indonesia is still lagging behind compared to Malaysia, Thailand and Singapore. The number of entrepreneurs in Indonesia must be increased immediately. Growing the number of entrepreneurs in Indonesia is our shared responsibility. Efforts to increase this can be done early on, namely at the high school level students. Entrepreneurial practice activities are limited and there is a lack of student understanding of how to start a business, so it is necessary to diversify entrepreneurial practice activities so that students have an understanding of starting a business. The service team carries out training activities for preparing business plan proposals to increase students' understanding of starting a business, the methods to be used are Observations, Lectures, Practices, Discussions, Surveys. The results of community service activities show that training activities for preparing business plan proposals can increase students' understanding of starting a business.